Penerapan Metode Waterfall Dan Webqual 4.0 Pada Pengembangan Website Dealer Asa Mandiri Motor - Meldy Saimon Pinontoan; Antonius Rachmat; Rosa Delima (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Abstract — Asa Mandiri Motor Dealer is one of the companies involved in the sale and purchase of used motorcycles. The problem that occurs at Asa Mandiri Motor Dealer is the decline in customer visits due to the lack of strategic location of the main dealer. The purpose of establishing a system for developing Asa Mandiri Motor dealer through the Waterfall method website is to measure the quality level using the webqual 4.0 method and the Importance Performance Analysis (IPA) to determine the assessment tests and improvements that are required to improve the service to users and customers through the website.In this study, the author also tested the waterfall method using black box testing to determine the level of functionality on the site, and using tests on the quality level of the site to make recommendations for improvements through quadrant analysis in the Webqual 4.0 method and the Importance Performance Analysis (IPA). This test was conducted on 50 respondents based on the type of respondent (client, non-client (general public), administrator). The results of the study show that the website can be accessed online, the level of website functionality that meets the design requirements, still has a gap value of -0.07, which means that the site is still not in accordance to the needs of users with relatively small scores and author has made improvements to the indicators (INF1, INF2, INF3, USA4, USA5), but no further testing has been done. Keywords— Waterfall, Webqual 4.0, Importance Analysis, Black Box Test